Manajemen Prilaku Berhubungan dengan Hidup Bersih dan Sehat - Ardayani, Tri; Rejeki, Sri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the relationship between behavioral management related to clean and healthy living. The method used is quantitative with a descriptive survey method research design. The results of the research show that some of the respondents have a poor level of knowledge, the majority of respondents have a poor economic status, the majority of respondents stated that cadres support the implementation of the clean and healthy living behavior program, the majority of respondents indicated that health workers support the performance of the program clean and healthy living behavior, the majority of respondents have unhealthy clean and healthy living behavior. In conclusion, there is a relationship between the level of knowledge and economic status and clean and healthy living behavior in the household setting of the Cipageran subdistrict, and there is no relationship between the role of cadres and the part of health workers with clean and healthy living behavior in the household setting of Panjunan subdistrict. Keywords: Management, Clean and Healthy Living Behavior